PREVALENCE OF THALASSEMIA GENES IN MOSUL - Khaleel, Khaleed; Hameed, Athraa; Fadhel, Ayad; Yaseen, Nahi (Iraqi Journal of Science, 2025)
To estimate the prevalence of the thalassemia genes in Mosul city, a study wascarried out on ٣٧٥ persons randomly selected, from people attending three majorhospitals in the city.A reduced mean cell volume (MCV) below ٨٠ fl was used as screening test forthalassemia genes (e.g. hemoglobin, Hb. Electrophoresis, and finally blood Ironcontent).A total of ٣٣ cases (٨.٨%) were found carrying thalassemia genes. From the abovecases, ٢٥ cases (٦.٧%) were beta-thalassemia trait ٨ cases (٢.١%) were alphathalassemia.